DEVS for AUTOSAR-based system deployment modeling and simulation. (June 2017) - Denil, Joachim; De Meulenaere, Paul; Demeyer, Serge; Vangheluwe, Hans
AUTOSAR (AUTomotive Open System ARchitecture) is an open and standardized automotive software architecture, developed by automobile manufacturers, suppliers, and tool developers. Its design is a direct consequence of the increasingly important role played by software in vehicles. As design choices during the software deployment phase have a large impact on the behavior of the system, designers need to explore various trade-offs. Examples of such design choices are the mapping of software components to processors, the priorities of tasks and messages, and buffer allocation. In this paper, we evaluate the appropriateness of DEVS, the Discrete-Event System specification, for modeling and subsequent performance evaluation of AUTOSAR-based systems. Moreover, a DEVS simulation model is constructed for AUTOSAR-based electronic control units connected by a communication bus. To aid developers in evaluating a deployment solution, the simulation model is extended with co-simulation with a plant and environment model, evaluation at different levels of detail, and fault injection. Finally, we examine how the simulation model supports the relationship between the supplier and the original equipment manufacturer in the automotive industry. We demonstrate and validate our work by means of a power window case study.